A MODIFIED DHILLON DISTRIBUTION: PROPERTIES AND APPLICATION - Iliyasu, A. S.; Ishaq, O. O.; Abduhamid, A. O.; Ibrahim, A.; Abubakar, S. S.; Musa, U. M.; Ahmed, S.; Usman, A.; Abba, B. M. (FUDMA JOURNAL OF SCIENCES, 2024)
There are still a lot of real-world issues where the observed facts cannot effectively fit into frequently used classical probability models. To solve this, it is imperative to provide probability models that accurately represent the behavior of certain real-world phenomena. having considered these problems, the study proposed a new lifetime distribution, the Modified Dhillon Distribution (MDD), developed using the Beta integrated model approach. The study examines the statistical properties of the new distribution such as the Quantile function, Moment, Moment generating function, Entropy, and reliability functions. Moreover, the maximum likelihood approach was used to estimate the distribution parameters. Using real data, the study demonstrates the applications of the MDD using two sets of real data sets, and it has the minimum value of AIC, BIC and CAIC. Therefore, based on the results the study concluded that the MDD offers the best fit out of all the competing distributions.